Organic carbon remobilized from thawing permafrost is resequestered by reactive iron on the Eurasian Arctic Shelf; Geophysical Research Letters; Vol. 42, iss. 19 - Salvado J. A. Joan; Tesi T.; Andersson A.; Ingri J.; Dudarev O. V. Oleg Viktorovich; Semiletov I. P. Igor Petrovich; Gustafsson O. (2015, 2015)
Title screen